Pengaruh Country of Origin dan Brand Image terhadap Keputusan Pembelian Iphone di Fakultas Ekonomi Kampus Palembang Universitas Sriwijaya - Azzahra, Nafinka; Putri, Yulia Hamdaini; Maulana, Ahmad (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of Country Of Origin and Brand Image on iPhone product purchasing decisions. The research method used is a quantitative method. The data used in this research is primary data. The sampling technique uses a non-probability sampling technique. The samples studied in this study were 100 respondents who were active students of the Faculty of Economics, Palembang Campus, Sriwijaya University. Based on the statistical t test conducted, it can be concluded that the country of origin variable partially has a significant effect on the decision to purchase an iPhone as indicated by a significance value of 0.007 <0.05. Based on the statistical t-test conducted, it can be concluded that the brand image variable partially has a significant effect on the decision to purchase an iPhone as indicated by a significance value of 0.002 <0.05. Based on the simultaneous f test, a significance value of 0.000 <0.05 was obtained, so it can be concluded that country of origin and brand image as a whole have a significant effect on iPhone purchasing decisions. The magnitude of the influence of the independent variable on the dependent variable is 37.7%, the remaining 62.3% is influenced by other variables outside the research.Keywords: Author Guidelines; Journal Al-Kharaj; Article Templates. Keywords : Country Of Origin, Brand Image, Purchase Decision